GLOBALLASHUV SHARAOITIDA TA’LIM-TARBIYA MASALALARI - Egamberdiyev Oyatillox Alisher o‘g‘li, Muhammadjonova O‘g‘iloy Bahodirjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides information about globalization and the place and role of this process in the issue of education and training, as well as the advantages of the process of globalization and how important this process is in the issue of education and training. .